Assessing the impacts of mitigation and geoengineering intervention scenarios on Earth system dynamics and climatological variability with multimodal simulations - Bradley A. Gay; Lukas Mandrake; Kimberley R. Miner; Charles E. Miller (Scientific Reports)
Abstract Given a world increasingly dominated by climate extremes, modifying the Earth’s climate with large-scale geoengineering intervention is inevitable. However, geoengineering faces a conundrum: forecasting the consequences of climate intervention accurately in a system for which we have incomplete observations and an imperfect understanding. We evaluate the global response and potential implications of mitigation and intervention deployment by utilizing CRU TS4.08 observations, ERA5 reanalysis data, and CMIP6 scenario-based UKESM0-1-LL simulations. From 1950 to 2022, global weighted mean surface temperature (Tsurf) and total precipitation (P) rose by 1.37 $$\:±\:$$ 0.48 °C and 0.05 $$\:±\:$$ 0.57 mm day-1. Significant regional Tsurf anomalies and erratic interannual variability of P were revealed, with ranges from 7.63 °C in Greenland and northern Siberia to -2.38 °C in central Africa and 1.17 mm day-1 in southern Alaska to -1.20 mm day-1 in Colombia and east Africa. Collectively, mitigation and intervention simulations tended to overestimate the variability and magnitude of Tsurf and P, exhibiting substantial regional discrepancies and scenario-specific heterogeneity when estimating atmospheric methane concentration ([CH4]). Despite capturing significant departures in Tsurf, P, and [CH₄], replicating historical P teleconnections and spatial patterns of warming remained a challenge. These results underscore regional disparities with global implications, harkening the necessity to refine existing architectures while developing novel methods to evaluate the risks and feasibility of geoengineering intervention.